PENGARUH KESADARAN HALAL DAN RELIGIUSITAS TERHADAP KEPUTUSAN KONSUMEN PADA KLINIK KECANTIKAN MUSLIMAH - Agatha Christy Situru (Nusantara Hasana Journal, 2025)
The growing variety of beauty products is an advantage for consumers because they have many alternative choices to choose from. This makes it necessary for beauty clinics to read consumer desires in order to have loyal customers. The aim of this research is to determine the positive influence of halal awareness and religiosity on consumer decisions in choosing a Muslim beauty clinic. This research is quantitative research using a survey method. The population in this study were female consumers who were in Trenggalek Regency, East Java and had used Muslimah beauty clinic products and services. The sampling technique used a purposive sampling method with a sample size of 150 people. The results of this study indicate that halal awareness and religiosity have a positive influence on consumer decisions in choosing a Muslim beauty clinic. These results confirm that halal awareness is an important factor for Muslim consumers to evaluate products and convince them of the quality of the products being sold. In addition, with the large diversity of beauty products available, companies must pay attention to the value of religiosity as part of measuring a person's Islamic faith and contribute to determining purchasing decisions.